IMPROVING STUDENTS’ OF NON-ENGLISH DEPARTMENT PERSPECTIVE IN LEARNING VOCABULARY THROUGH WEBSITE - Risa Mufliharsi; Eva Nurul Candra (English Education Department, 2017)
The research purposes to improve students’ of non English department perspective in learning vocabulary through ESP syllabus which implemented in website that suitable with visual design communication program. The research uses qualitative data to find out credible data which have been confirmed by the writers. Then, the writers analyze the data which have been taken . The research is conducted in visual design communication program of UNINDRA in first grade students that consisted by 45 students. The procedure of collecting the data:1) Writers observed by taking Mid Term Scores, 2) Writers checked the syllabus designed, 3) Writers found out the need analysis of using ESP materials by using questionare, 4) Writers analyzed the data, 5) Writers grouped the data, 6) Writers designed syllabus and the course, 7) The writer developed the material which students need, 8) The writer evaluated the students’ result. The result of this research is writers got evaluation from the students for knowing their concerning in learning English through website by doing interview. There are five questions and the students can answer it directly refers to their satisfaction, their interest, their need, their achievement, and their suggestions. Based on the students’ answers, 80 percents of students enjoy this course and can increase their vocabulary naturally.